2012
DOI: 10.4103/0971-4065.98755
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of renal function between normal-weight and overweight children

Abstract: Obesity in children is associated with hypertension, dyslipidemia, cardiovascular disease, diabetes mellitus, colon cancer, and kidney disease. Most of the studies that evaluate the association between obesity and kidney disease have been done in adults. This study was planned to compare renal function between normal-weight and overweight children. In this case-control study, 92 children (45 boys, 47 girls) aged 7-12 years were included in the analysis. 46 children (23 boys, 23 girls) with BMI 85th percentile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
1
1
1
Order By: Relevance
“…Two serum biomarkers, serum creatinine and blood urea are commonly used to discover kidney toxicity do not change quickly during the presentation of acute conditions (19) . In study conducted by (20) and (21) no significant differences in creatinine revealed between normal and obese children these differences with our results may be due to the difference in localities, sample size, cultural and/or socioeconomic causes.…”
Section: Discussioncontrasting
confidence: 66%
“…Two serum biomarkers, serum creatinine and blood urea are commonly used to discover kidney toxicity do not change quickly during the presentation of acute conditions (19) . In study conducted by (20) and (21) no significant differences in creatinine revealed between normal and obese children these differences with our results may be due to the difference in localities, sample size, cultural and/or socioeconomic causes.…”
Section: Discussioncontrasting
confidence: 66%
“…Hypertension and diabetes may decrease renal clearance. A study of 46 overweight children (BMI 85th percentile or higher) matched to 46 normal‐weight controls demonstrated lack of significant differences in GFR, serum creatinine, albuminuria, and calciuria …”
Section: Methodsmentioning
confidence: 99%
“…Δληνχηνηο, ην ηνπίν νχηε εδψ είλαη μεθάζαξν κε ηα απνηειέζκαηα ησλ δηαθφξσλ εξεπλψλ ζηε βηβιηνγξαθία λα είλαη ζπγρπηηθά. ε ζρνιηθή κειέηε δηελεξγεζείζα ζηε Νηγεξία αλαθέξεηαη κηα ζεηηθή ζπζρέηηζε αλάκεζα ζηε ΜΑ θαη ην ΓΜ (chi square= 0,16, p= 0,669),49 ελψ ε κειέηε ησλ Falakaflaki θαη ζπλ πνπ ζρεδηάζηεθε γηα λα ζπγθξίλεη ηε λεθξηθή ιεηηνπξγία ζε ππέξβαξα θαη θπζηνινγηθνχ βάξνπο παηδηά δελ απνθάιπςε δηαθνξά φζν αθνξά ηελ αιβνπκηλνπξία αλάκεζα ζηηο δχν νκάδεο 87. Δηδηθφηεξα ζηελ αλάιπζε πνπ πξαγκαηνπνηήζεθε ρξεζηκνπνηψληαο δεδνκέλα απφ ηε NHANES, ε παξνπζία ΜΑ ζηνπο κε παρχζαξθνπο εθήβνπο ζρεηίζηεθε κφλν κε ηελ παξνπζία δηαβήηε, ελψ ε γιπθφδε λεζηείαο, ν δείθηεο ΖΟΜΑ, ε ππέξηαζε, ν δηαβήηεο θαη ην θάπληζκα ζπζρεηίζηεθαλ ζεκαληηθά κε ηε ΜΑ ζηνπο παρχζαξθνπο εθήβνπο, γεγνλφο πνπ είλαη πηζαλφ λα αληαλαθιά ηε δηακεζνιαβνχκελε απφ ην κεηαβνιηζκφ ηεο γιπθφδεο ή ηεο ηλζνπιίλεο ζρέζε κεηαμχ παρπζαξθίαο θαη ΜΑ 83.…”
unclassified